Synergistic enhancement of heavy rare earth elements leaching from ion-adsorption rare earth ores using fungal metabolites supplemented with ammonium sulfate - Yun Fang; Hailan Wang; Linlin Yan; Jianxiong Zeng; Siqi Chen; Jun Liu; Guowei Wang; Yang Liu; Jun Wang; Chunqiao Xiao (Hydrometallurgy, 2026)

Prescription principle, phytochemistry, pharmacological activities and clinical applications of Huangqin decoction: a comprehensive review - Yan Fang; Haizhen Liang; Linlin Lu; Xijie Tian; Yuting Zhang; Junyu Zhang; Zhifeng Dai; Xiaojuan Chen; Juan Song; Tao Su; Zhongqiu Liu; Baiping Ma (Phytochemistry Reviews, 2026)

Insights into Cronobacter sakazakii adaptation to Benzalkonium chloride: virulence assessment and transcriptomics analysis - Hongmei Niu; Xiang Wang; Yuan Wang; Xiaojie Qin; Lei Fang; Jianwen Gao; Yanqi Zhou; Linlin Xiao; Qingli Dong (Food Research International, 2026)

LDH-based avermectin nanopesticide modulates bioaccumulation, antioxidant responses, and microbiota stability in earthworms' gut - Shuting Yang; Yiqiong Li; Chao Zong; Xinglu Pan; Haonan Wang; Qingkui Fang; Linlin Shi; Fengshou Dong; Haiqun Cao (Pesticide Biochemistry and Physiology, 2026)

Holocene wildfire activity archived in East Asian marginal sea: Linkages to climate variability and human civilization - Linlin Chen; Yazhi Bai; Zhigang Guo; Weini Chong; Yuying Zhang; Jinming Bai; Yaru Liu; Haiyan Fang; Limin Hu (CATENA, 2026)

A Deep-Sea Multi-Sequence Sampling System Integrating In Situ Microbial Filtration with Rapid RNA Stabilization - Wei Bu; Yuan-Jie Chen; Jinhai Luo; Linlin Sun; Xiang Li; Xinyuan Gao; Yuanli Fang; Leisheng Tang; Jiaying Zhao; Jingchun Feng; Haocai Huang (Journal of Marine Science and Engineering, 2026)
Rapid depressurization and warming during recovery can trigger stress in deep-sea microbes and accelerate RNA degradation. We developed a remotely operated vehicle (ROV)-oriented multi-sequence microbial sampler for 2000 m sampling (20 MPa, 2 °C) that integrates in situ filtration with immediate RNAlater injection (an RNA stabilization reagent), collecting up to 12 samples per dive. A Dirichlet sampling–B-spline–SVM framework was used to optimize the cam profile of the sequence trigger for robust actuation under geometric constraints and realistic tolerances in both manufacturing and assembly. Relative to the baseline 3-4-5 motion law, the optimized design reduces nominal peak driving torque by ~18–20% and lowers the maximum torque under tolerance perturbations; tests show a further ~10–25% reduction using a SiC ball–ZrO2 block pair versus a MoS2-lubricated titanium pushrod–ZrO2 block pair. A Darcy–Forchheimer porous-media computational fluid dynamics (CFD) model predicts earlier clogging on the lower membrane and a fast-to-slow RNAlater displacement process; greater membrane resistance mismatch delays 95% displacement and increases RNAlater loss. Simulations and Rhodamine B tests suggest an RNAlater consumption of 0.9 L per parallel filter (one membrane per side), and 20 MPa chamber tests confirm stable operation and membrane retrieval.

Machine learning based prediction of mechanical properties in carbon fiber recovered through pyrolysis - Xiang Guo; Tian Li; Chunting Liu; Meng Zhang; Hao Li; Jinrui Li; Yihua Zhang; Chunmei Zeng; Shuwu Wei; Linlin Pei; Fang Liu; Da Chen (Waste Management, 2026)

O2-supplementing photosensitizer AuNCs@TAT as a highly efficient NIR-II-controllable pyroptosis inducer for cancer photoimmunotherapy - Linlin Xie; Xingye Ma; Zheng Wang; Caifang Wang; Zhongxin Xiao; Ling-Dong Sun; Chun-Hua Yan; Chen-Jie Fang (Chemical Engineering Journal, 2026)

Meso–Neoproterozoic rift system along the southwestern North China Craton: evidence from recent drilling and seismic data - Zhenhong Li; Xiaopeng Dong; Haifeng Bai; Yijun Zhou; Jiawei Cui; Linlin Kou; Fang Wu (International Geology Review, 2026)

Bone mesenchymal stem cells attenuate axonopathy in spinal cord of rats exposed to 2,5-hexanedione via NGF-dependent and -independent pathways - Qiufang Bai; Zhe Li; Jing Chen; Man Liu; Xiaodan Shao; Xiaochi Chen; Fengyuan Piao; Linlin Fang (Molecular and Cellular Biochemistry, 2026)

Dynamic reversible thermochromic camouflage smart textiles for temperature visualized personal healthcare and thermal management - Weiyi Zhang; Shuo Luan; Yuyan Fang; Linlin Zhu; Yang Yang; Mingwei Tian; Lijun Qu; Tingting Fan; Jinlei Miao (Chemical Engineering Journal, 2025)

Salvianolic Acid B and Ginsenoside Rg1 Combination Attenuates Cerebral Edema Accompanying Glymphatic Modulation - Lingxiao Zhang; Yanan Shao; Zhao Fang; Siqi Chen; Yixuan Wang; Han Sha; Yuhan Zhang; Linlin Wang; Yi Jin; Hao Chen; Baohong Jiang (Neuroscience Bulletin, 2025)

Hyperbaric oxygen treatment mitigates gut dysbiosis of mice with spinal cord injury - Mo Liu; Lu Yang; Ding Nan; Linlin Ma; Jing Zhang; Fang Liang; Jing Yang; Xuehua Liu (Journal of Molecular Medicine, 2025)

Land use carbon emission projections in shared socioeconomic and representative concentration pathways: Relationship with urbanization in Chinese megacities - Yu Yao; Linlin Lu; Zongtang Fu; Fang Chen; Ran Wang; Qingting Li (Land Use Policy, 2025)

An improved method for extracting cellulose from fossil wood and its paleoclimatic implications - Donghao Wu; Xin Wang; Yang Deng; Mi Wang; Gang Hu; Xuan Ding; Linlin Gao; Keyan Fang; Xiaohua Gou (Frontiers of Earth Science, 2025)

Norgestrel shows androgenic properties and triggers reproductive neuroendocrine toxicity in the testes of Pacific oysters (Crassostrea gigas) - Yan Fang; Baojun Liu; Juan Wang; Haoyang Zhong; Linlin Fan; Yuchao Huang; Changkun Chen; Songtao Lu; Tao Zheng (Journal of Hazardous Materials, 2025)

Holocene seismically induced soft-sediment deformation structures in the Qingshuihe Basin, northeastern Tibetan Plateau - Ting Huang; Zhenhong Li; Xiaopeng Dong; Zhonghai Wu; Linlin Kou; Fang Wu (Sedimentary Geology, 2025)

The Physiological and Flavonoid Metabolism of the Tea Plant in Response to Nitrogen Nutrition is Regulated by the Ultraviolet-B Radiation Environment - Fang Dong; Hua Zhang; Linlin Liu; Jianyun Ruan; Meiya Liu; Qunfeng Zhang (Journal of Plant Growth Regulation, 2025)

MVPCR: Multiplex Visual Detection Strategy Based on Ultrafast PCR for Point-of-Care Pathogens Detection Within 10 Min - Ziqin Zhang; Cui Wu; Linlin Bai; Kaiming Guo; Ting Wang; Dianwei Liu; Mingrui Zhu; Feng Qian; Fang Zhang; Rui Wang (Phenomics, 2025)

Spegazzinia menglaensis, A Novel Species of Didymosphaeriaceae from Air in China - Xingwen Dai; Linlin Fang; Tong Chen; Manyao Feng; Zefen Yu (Current Microbiology, 2025)

Cation Channel TMEM63A Autonomously Facilitates Oligodendrocyte Differentiation at an Early Stage - Yue-Ying Wang; Dan Wu; Yongkun Zhan; Fei Li; Yan-Yu Zang; Xiao-Yu Teng; Linlin Zhang; Gui-Fang Duan; He Wang; Rong Xu; Guiquan Chen; Yun Xu; et al. (Neuroscience Bulletin, 2025)
Accurate timing of myelination is crucial for the proper functioning of the central nervous system. Here, we identified a de novo heterozygous mutation in TMEM63A (c.1894G>A; p. Ala632Thr) in a 7-year-old boy exhibiting hypomyelination. A Ca 2+ influx assay suggested that this is a loss-of-function mutation. To explore how TMEM63A deficiency causes hypomyelination, we generated Tmem63a knockout mice. Genetic deletion of TMEM63A resulted in hypomyelination at postnatal day 14 (P14) arising from impaired differentiation of oligodendrocyte precursor cells (OPCs). Notably, the myelin dysplasia was transient, returning to normal levels by P28. Primary cultures of Tmem63a −/− OPCs presented delayed differentiation. Lentivirus-based expression of TMEM63A but not TMEM63A_A632T rescued the differentiation of Tmem63a −/− OPCs in vitro and myelination in Tmem63a −/− mice. These data thus support the conclusion that the mutation in TMEM63A is the pathogenesis of the hypomyelination in the patient. Our study further demonstrated that TMEM63A-mediated Ca 2+ influx plays critical roles in the early development of myelin and oligodendrocyte differentiation.

Identification and characterization of ClAPRR2, a key candidate gene controlling watermelon stripe color - Shuang Liang; Miaomiao Yang; Linlin Zhang; Xufeng Fang; Xian Zhang; Chunhua Wei; Zuyun Dai; Zhongzhou Yang; Chaonan Wang; Bin Liu; Feishi Luan; Shi Liu (Plant Science, 2025)

TRIM21 Promotes Endothelial Cell Activation via Accelerating SOCS3 Ubiquitination Degradation in Atherosclerosis - Zhenxuan Hao; Yihuan Wang; Linlin Chen; Yanjun Zhou; Dezhou Fang; Wenxiang Yao; Lili Xiao; Yanzhou Zhang (Cardiovascular Toxicology, 2025)

Stability and sensory quality of plant-based milk substitutes made from 36 different oat varieties: Relation with oat kernels attributes - Lulu Cui; Jiani Zhao; Linlin Fan; Aijinxiu Ma; Fang Zhong; Sumei Zhou; Dianzhi Hou (Journal of Cereal Science, 2025)

Widespread presence of gut bacterium Glutamicibacter ectropisis sp. nov. confers enhanced resistance to the pesticide bifenthrin in tea pests - Xiayu Li; Ting Fang; Tian Gao; Hao Gui; Ying Chen; Linlin Zhou; Yong Zhang; Yunqiu Yang; Letian Xu; Yanhua Long (Science of The Total Environment, 2024)

Environmental exposure patterns to 94 current-use pesticides in women of reproductive age who are preparing for pregnancy - Tian Tian; Fang Liu; Yu Fu; Junjie Ao; Shujian Lin; Qianhui Cheng; Kalbinur Kayim; Fei Kong; Linlin Wang; Xiaoyu Long; Yuanyuan Wang; Jie Qiao (Science of The Total Environment, 2024)

Integrated assessment of trace elements in a marine ranching area based on multi-species and multi-level biomarkers: a case study in China’s national-level marine ranching demonstration area - Mingzhu Li; Zhixu Chen; Ming Li; Jiugang Zhang; Bingqing Xu; Yanyan Yang; Xiangfei Li; Linlin Fan; Baojun Liu; Tao Zheng; Yan Fang; Fan Li (Frontiers in Marine Science, 2024)
The goal of this study was to evaluate the trace element pollution in a marine ranching area in China based on molecular responses (expression of metallothionein and antioxidant enzyme genes), and biochemical biomarkers (metallothionein content, antioxidant enzyme activities, and malonaldehyde level) in four indicator species. We collected samples of two fish ( Lateolabrax maculatus and Sebastes schlegelii ), one crustacean ( Charybdis japonica ), and one gastropod ( Rapana venosa ) from the western Furong Island marine ranching area and from an adjacent area in March 2022 and measured the trace element content in these indicator species as well as in the seawater and sediment. We found that the bioaccumulation characteristics of trace elements and the response patterns of biomarkers were species specific. Moreover, not every biomarker was significantly correlated with environmental trace element content. We then established two biomarker combinations indicative of trace element pollution in seawater and sediment, respectively, based on the correlation between biomarkers and trace element contents. The selected biomarkers were integrated using integrated biomarker response version 2 (IBRv2). IBRv2 values in the studied marine ranching area were lower than those in the adjacent area. Additionally, these values were consistent with the bioaccumulation of trace elements in the indicator species, the integrated trace element pollution index for seawater, and the potential risk index for sediment. These results show that this multi-biomarker and multi-species IBRv2 approach provided a comprehensive diagnosis of trace element pollution in the marine ranching area. Therefore, its application may be beneficial for marine environmental monitoring and management in view of the ecotoxicological impact of pollutants on organisms.

Evidence and causes of recent decreases in nitrogen deposition in temperate forests in Northeast China - Yingying Wang; Feifei Zhu; Jin Li; Geshere Abdisa Gurmesa; Shaonan Huang; Xiaoming Fang; Dongwei Liu; Abubakari Said Mgelwa; Wenchao Wang; Kai Huang; Yihang Duan; Linlin Song; et al. (Science of The Total Environment, 2024)

Role of microalgae-bacterial consortium in wastewater treatment: A review - Lixin Li; Wei Chai; Caiyu Sun; Linlin Huang; Tao Sheng; Zhiwei Song; Fang Ma (Journal of Environmental Management, 2024)

Nitrogen isotopic characteristics of aerosol ammonium in a Chinese megacity indicate the reduction from vehicle emissions during the lockdown period - Zhengjie Li; Hongwei Xiao; Wendell W. Walters; Meredith G. Hastings; Juan Min; Linlin Song; Weizhi Lu; Libin Wu; Wende Yan; Shuguang Liu; Yunting Fang (Science of The Total Environment, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Duck Tembusu virus infection activates the MKK3/6-p38 MAPK signaling pathway to promote virus replication - Yuting Cheng; Linlin Jiao; Jinying Chen; Peiyao Chen; Fang Zhou; Jilin Zhang; Mixue Wang; Qingguo Wu; Shinuo Cao; Huipeng Lu; Zhi Wu; Anping Wang; et al. (Veterinary Microbiology, 2024)

Patterns and drivers of atmospheric inorganic nitrogen deposition in Northeast Asia - Abubakari Said Mgelwa; Feifei Zhu; Dan Huang; Linlin Song; Yingying Wang; Geshere Abdisa Gurmesa; Ang Wang; Miao Liu; Shaonan Huang; Qingyan Qiu; Hiroyuki Sase; Weixing Zhu; et al. (Journal of Environmental Management, 2024)

2-Methoxyestradiol ameliorates paraquat-induced pulmonary fibrosis by inhibiting the TGF-β1/Smad2/3 signaling pathway - Linlin Hou; Fang Yang; Yan Zhang; Yi Li; Hongyi Yan; Cuicui Meng; Yuqi Du; Huanzhou Zhu; Ding Yuan; Yanxia Gao (Pesticide Biochemistry and Physiology, 2023)

Geranylgeranylacetone, an inducer of heat shock protein 70, attenuates pulmonary fibrosis via inhibiting NF-κB/NOX4/ROS signalling pathway in vitro and in vivo - Rong Zhou; Chaomei Jin; Linlin Jiao; Siyu Zhang; Mei Tian; Jiamin Liu; Songtai Yang; Wu Yao; Fang Zhou (Chemico-Biological Interactions, 2023)

GGA (geranylgeranylacetone) ameliorates bleomycin-induced lung inflammation and pulmonary fibrosis by inhibiting apoptosis and oxidative stress - Rong Zhou; Chaomei Jin; Linlin Jiao; Siyu Zhang; Mei Tian; Jiamin Liu; Songtai Yang; Wu Yao; Fang Zhou (Molecular Biology Reports, 2023)

The effect of SARS-CoV-2 infection on human embryo early development: a multicenter prospective cohort study - Xiaolei Chen; Huangcong Shi; Cheng Li; Wanxia Zhong; Linlin Cui; Wenjun Zhang; Ling Geng; Kuona Hu; Mei Fang; Daimin Wei; Junhao Yan; Yun Sun; et al. (Science China Life Sciences, 2023)

Simultaneous oxidation and absorption of nitric oxide and sulfur dioxide by peroxymonosulfate activated by bimetallic metal-organic frameworks - Zhaoxin Wan; Xiude Hu; Chengbo Li; Jiawei Zhang; Qi Wang; Long Fang; Linlin Zhang; Qingjie Guo; Deshuai Sun (Journal of Environmental Chemical Engineering, 2023)

A rapid and sensitive single-cell proteomic method based on fast liquid-chromatography separation, retention time prediction and MS1-only acquisition - Wei Fang; Zhuokun Du; Linlin Kong; Bin Fu; Guibin Wang; Yangjun Zhang; Weijie Qin (Analytica Chimica Acta, 2023)

Relationships between denitrification rates and functional gene abundance in a wetland: The roles of single- and multiple-species plant communities - Yushuang Kong; Haikuo Zhang; Linlin Tian; Junji Yuan; Youchao Chen; Yan Li; Jian Chen; Scott X. Chang; Yunying Fang; Ehsan Tavakkoli; Yanjiang Cai (Science of The Total Environment, 2023)

Global, regional, and national deaths, disability-adjusted life years, years lived with disability, and years of life lost for the global disease burden attributable to second-hand smoke, 1990–2019: A systematic analysis for the Global Burden of Disease Study - Chunxia Zhai; Dingtao Hu; Guanghui Yu; Wanqin Hu; Qiqun Zong; Ziye Yan; Yuhua Wang; Linlin Wang; Tingyu Zhang; Hongyu Sun; Ling Cai; Liangyu Cui; et al. (Science of The Total Environment, 2023)

Phthalate Mixture Exposure is Associated with Elevated Blood Pressure in Chinese Children: A Panel Study - Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Huihua Yang; Meng Li; Shuang Chen; Jie Yu; Qin Fang; Xuefeng Lai; Liangle Yang; Rui Zhu; et al. (Exposure and Health, 2023)

Crop type mapping in the central part of the North China Plain using Sentinel-2 time series and machine learning - Ke Luo; Linlin Lu; Yanhua Xie; Fang Chen; Fang Yin; Qingting Li (Computers and Electronics in Agriculture, 2023)

Interaction mechanisms of fouling and cleaning protocol for A/O-MBR treatment of coal⁃to⁃hydrogen wastewater - Fang Gao; Lingyun Li; Yanwei Shi; Xiaofei Xue; Jianhua Mao; Linlin Xing; Xiaoyan Yao (Process Safety and Environmental Protection, 2023)

Tumor necrosis factor-α coordinates with transforming growth factor-β1 to induce epithelial-mesenchymal transition and migration via the NF-κB/NOX4 pathway in bronchial epithelial cells - Ke Li; Rong Zhou; Mingze Ma; Chaomei Jin; Linlin Jiao; Siyu Zhang; Mei Tian; Fang Zhou (Molecular Biology Reports, 2022)

Associations of urinary polycyclic aromatic hydrocarbon metabolites and blood pressure with the mediating role of cytokines: A panel study among children - Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Huihua Yang; Jie Yu; Shuang Chen; Meng Li; Qin Fang; Xuefeng Lai; Liangle Yang; Rui Zhu; et al. (Environmental Science and Pollution Research, 2022)

Metabolism and pharmacokinetics of mebendazole in Japanese pufferfish ( Takifugu rubripes ) - Lei Men; Yuhan Zhang; Keke Li; Zhongyu Li; Chunbin Li; Xueyuan Zhang; Xiaojie Gong; Linlin Fang (Food Additives & Contaminants: Part A, 2022)

A July-August relative humidity record in North China since 1765 AD reconstructed from tree-ring cellulose δ18O - Linlin Cui; Yu Liu; Qiang Li; Huiming Song; Congxi Fang (International Journal of Biometeorology, 2021)

Biomechanical Regulation of Stem Cell Fate - Linlin Jin; Ping Wang; Fang Ni (Current Stem Cell Reports, 2021)

Revisiting the Concentration Observations and Source Apportionment of Atmospheric Ammonia - Yuepeng Pan; Mengna Gu; Yuexin He; Dianming Wu; Chunyan Liu; Linlin Song; Shili Tian; Xuemei Lü; Yang Sun; Tao Song; Wendell W. Walters; Xuejun Liu; et al. (Advances in Atmospheric Sciences, 2020)

Evaluation of Genomic Selection for Seven Economic Traits in Yellow Drum (Nibea albiflora) - Guijia Liu; Linsong Dong; Linlin Gu; Zhaofang Han; Wenjing Zhang; Ming Fang; Zhiyong Wang (Marine Biotechnology, 2019)
Yellow drum ( Nibea albiflora ) is an important maricultural fish in China, and genetic improvement is necessary for this species. This research evaluated the application of genomic selection methods to predict the genetic values of seven economic traits for yellow drum. Using genome-wide single-nucleotide polymorphisms (SNPs), we estimated the genetic parameters for seven traits, including body length (BL), swimming bladder index (SBI), swimming bladder weight (SBW), body thickness (BT), body height (BH), body length/body height ratio (LHR), and gonad weight index (GWI). The heritability estimates ranged from 0.309 to 0.843. We evaluated the prediction performance of various statistical methods, and no one method provided the highest predictive ability for all traits. We then evaluated and compared the use of genome-wide association study (GWAS)–informative SNPs and random SNPs for prediction and found that GWAS-informative SNPs obviously increased. It only needed 5 and 100 informative SNPs for LHR and BT to achieve almost the same predictive abilities as using genome-wide SNPs, and for BL, SBI, SBW, BH, and GWI, about 1000 to 3000 informative SNPs were needed to achieve whole-genome level predictive abilities. It can be concluded from the test results that breeders can use fewer SNPs to save the breeding costs of genomic selection for some traits.

Wheat methionine sulfoxide reductase A4.1 interacts with heme oxygenase 1 to enhance seedling tolerance to salinity or drought stress - Pengcheng Ding; Linlin Fang; Guangling Wang; Xiang Li; Shu Huang; Yankun Gao; Jiantang Zhu; Langtao Xiao; Jianhua Tong; Fanguo Chen; Guangmin Xia (Plant Molecular Biology, 2019)

Sodium Fluoride (NaF) Induces Inflammatory Responses Via Activating MAPKs/NF-κB Signaling Pathway and Reducing Anti-inflammatory Cytokine Expression in the Mouse Liver - Linlin Chen; Ping Kuang; Huan Liu; Qin Wei; Hengmin Cui; Jing Fang; Zhicai Zuo; Junliang Deng; Yinglun Li; Xun Wang; Ling Zhao (Biological Trace Element Research, 2019)

5-Azacytidine treatment and TaPBF-D over-expression increases glutenin accumulation within the wheat grain by hypomethylating the Glu-1 promoters - Jiantang Zhu; Linlin Fang; Jiaqi Yu; Ying Zhao; Fanguo Chen; Guangmin Xia (Theoretical and Applied Genetics, 2018)

Identification and Functional Analysis of Two Cotton Orthologs of MAX2 Which Control Shoot Lateral Branching - Linlin Zhao; Jingjing Fang; Jin Xing; Weina Liu; Peng Peng; Haixin Long; Jinfeng Zhao; Wenhui Zhang; Xueyong Li (Plant Molecular Biology Reporter, 2017)

Trivalent chromium alleviates oleic acid induced steatosis in SMMC-7721 cells by decreasing fatty acid uptake and triglyceride synthesis - Song Wang; Jian Wang; Xiaonan Zhang; Linlin Hu; Zhijia Fang; Zhiwei Huang; Ping Shi (BioMetals, 2016)

Heavy mineral assemblage characteristics and the Cenozoic paleogeographic evolution in southwestern Qaidam Basin - LinLin Li; ZhaoJie Guo; ShuWei Guan; SuPing Zhou; MingZhen Wang; YaNan Fang; ChenChen Zhang (Science China Earth Sciences, 2015)

High-throughput sequencing-based gene profiling on multi-staged fruit development of date palm (Phoenix dactylifera, L.) - Yuxin Yin; Xiaowei Zhang; Yongjun Fang; Linlin Pan; Gaoyuan Sun; Chengqi Xin; Mohammed M. Ba Abdullah; Xiaoguang Yu; Songnian Hu; Ibrahim S. Al-Mssallem; Jun Yu (Plant Molecular Biology, 2012)

Ice phase as an important factor on the seasonal variation of polycyclic aromatic hydrocarbons in the Tumen River, Northeastern of China - Linlin Cong; Yingyu Fang; Miao He; Xinshun Wang; Narayanan Kannan; Donghao Li (Environmental Science and Pollution Research, 2010)